Improving the Quality of Article Master Data --- Specification of an Integrated Master Data Platform for Promotions in Retail - Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian; Becker, Jörg (Proceedings of the 16th European Conference on Information Systems)

Entwicklung Serviceorientierter Architekturen zur Integration von Produktion und Dienstleistung --- Eine Konzeptionsmethode und ihre Anwendung am Beispiel des Recyclings elektronischer Geräte - Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Wirtschaftsinformatik)

Unternehmensbewertung für substanzsteuerliche Zwecke - eine empirische Analyse des Stuttgarter Verfahrens und alternativer Ansätze - Müller, Jens
Über 50 Jahre wurde das Stuttgarter Verfahren verwendet, um den Wert nicht börsennotierter Unternehmen für die Erbschaft-, Schenkung- und Vermögensteuer zu bestimmen. Durch das Urteil des Bundesverfassungsgerichts vom 07.11.2006 ist der Gesetzgeber verpflichtet, die Erbschaftsteuer zu reformieren und eine marktnahe Bewertung von Unternehmensvermögen sicherzustellen. Auf der Basis einer umfangreichen empirischen Analyse geht Jens Müller den Fragen nach, wie stark eine Bewertung durch das Stuttgarter Verfahren von Marktwerten abweicht und in welchen Fällen eine akzeptable Approximation des Marktwertes erreicht wird. In der Praxis wird das Multiplikatorverfahren häufig zur Bewertung nicht börsennotierter Unternehmen verwendet. Der Autor untersucht, in welcher Form dieses Verfahren auch für steuerliche Zwecke geeignet ist und zeigt auf, mit welchen Schätzfehlern zu rechnen ist.
Keywords: Steuer-; Rechnungs- und Prüfungswesen

Intuition and professional competence: Intuitive versus rational forecasting of the stock market - Harteis, Christian; Gruber, Hans (Vocations and Learning)

Emerging perspectives of workplace learning

The culture of learning from mistakes: How employees handle mistakes in everyday work - Harteis, Christian; Bauer, Johannes; Gruber, Hans (International Journal of Educational Research)

The workplace as learning environment: Introduction - Harteis, Christian; Billett, Stephen (International Journal of Educational Research)

How important is intuition for teaching expertise in the field of adult education? - Harteis, Christian; Gruber, Hans (Studies in the Education of Adults)

How Intuition Contributes to High Performance: An Educational Perspective. - Harteis, Christian; Koch, Tina; Morgenthaler, Barbara (US-China Education Review)

Lernende Region Cham Programmvertiefung II Kommunale Kooperation Waldmünchen - Gruber, Hans; Harteis, Christian; Paetz, Nadja-Verena; Keil, Stefanie

Lernen und Lehren im Erwachsenenalter - Gruber, Hans; Harteis, Christian (Lehrbuch Pädagogische Psychologie)

Auswirkungen einer Reform des Erbschaft-und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens-und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Unternehmensbesteuerung)
Auswirkungen einer Reform des Erbschaft-und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens-und Grundvermögen
Keywords: Erbschaft-und Schenkungsteuergesetz; Steueraufkommen; verkehrswertorientierte Bewertung von Unternehmens-und Grundvermögen

Reliable Evidence of Data Integrity from an Untrusted Storage Service - Stern, Claudius; Adelt, Philipp; Krummel, Volker; Ackermann, Marcel Rudolf (Fourth International Conference on Networking and Services (icns 2008))

Regional Determinants of Entrepreneurial Start-Ups in a Developing Country - Gries, Thomas; Naudé, Wim; Wood, Eric; Meintjes, Aloe (Entrepreneurship & Regional Development)

Trade and Endogenous Formation of Regions in a Developing Country - Gries, Thomas; Naudé, Wim (Review of Developing Economics)

A Browser-Based Kerberos Authentication Scheme - Gajek, Sebastian; Jager, Tibor; Manulis, Mark; Schwenk, Jörg (Computer Security - ESORICS 2008, 13th European Symposium on Research in Computer Security, Málaga, Spain, October 6-8, 2008. Proceedings)

On Black-Box Ring Extraction and Integer Factorization - Altmann, Kristina; Jager, Tibor; Rupp, Andy (Automata, Languages and Programming, 35th International Colloquium, ICALP 2008, Reykjavik, Iceland, July 7-11, 2008, Proceedings, Part II - Track B: Logic, Semantics, and Theory of Programming & Track C: Security and Cryptography Foundations)

On the Equivalence of Generic Group Models - Jager, Tibor; Schwenk, Jörg (Provable Security, Second International Conference, ProvSec 2008, Shanghai, China, October 30 - November 1, 2008. Proceedings)

Nutzung von selbstsignierten Client-Zertifikaten zur Authentifikation bei SSL/TLS - Jager, Tibor; Jäkel, Heiko; Schwenk, Jörg (Sicherheit 2008: Sicherheit, Schutz und Zuverlässigkeit. Konferenzband der 4. Jahrestagung des Fachbereichs Sicherheit der Gesellschaft für Informatik e.V. (GI), 2.-4. April 2008 im Saarbrücker Schloss.)

Association between long-term consumption of soft drinks and variables of bone modeling and remodeling in a sample of healthy German children and adolescents - Libuda, Lars; Alexy, Ute; Remer, Thomas; Stehle, Peter; Schoenau, Eckhard; Kersting, Mathilde (The American Journal of Clinical Nutrition)

China’s provincial disparities and the determinants of provincial inequality - Gries, Thomas; Redlin, Margarete

International integration and regional development in China - Gries, Thomas; Redlin, Margarete

Konsum von Erfrischungsgetränken und Entwicklung des Körpergewichts im Kindes- und Jugendalter – Gibt es eine Verbindung? - Libuda, Lars; Alexey, U.; Stehle, P.; Kersting, M. (Aktuelle Ernährungsmedizin)

DONALD News: Erfrischungsgetränke und Ernährungsqualität. - Libuda, Lars; Kersting, M. (Ernährungsumschau)

Effects of Breastfeeding on Trajectories of Body Fat and BMI throughout Childhood - Buyken, Anette; Karaolis-Danckert, Nadina; Remer, Thomas; Bolzenius, Katja; Landsberg, Beate; Kroke, Anja (Obesity)

Prevalence of Chronic Complications, Metabolic Control and Nutritional Intake in Type 1 Diabetes: Comparison Between Different European Regions - Toeller, M.; Buyken, Anette; Heitkamp, G.; Berg, G.; Scherbaum, W. (Hormone and Metabolic Research)

Ernährungsbildung in Unterricht und Schulprofil. Essen und Trinken in der Schule – Bildungschance und Beitrag zu sozialer Gerechtigkeit - Schlegel-Matthies, Kirsten (Ernährung, Kultur, Lebensqualität. Wege regionaler Nachhaltigkeit)

Private Lebensführung als Umgang mit Komplexität - ein schwer operationalisierbares Bildungsziel - Methfessel, B.; Ritterbach, U.; Schlegel-Matthies, Kirsten (.): Schwer messbare Kompetenzen. Herausforderungen für die empirische Fachdidaktik)

iBeCOOL - Extraction d'informations biographiques dans les textes financiers - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Proceedings of the Lexis and Grammar Conference 2008)
Ce papier présente le contexte linguistique et la modélisation de notre système iBeCOOL (Informations Biographiques Extraites à l’aide de COntextes Observés Linguistiquement) dédié à l’extraction d’informations biographiques dans les textes de la presse financière en langue anglaise. La notion d’événement biographique (tel que la naissance, le mariage, la carrière professionnelle) est caractérisée formellement par un schéma prédicatif à plusieurs arguments dont l’un étant une instance de la classe d’objets <Personne>. Notre approche consiste à décrire ces types de relations à l’aide de grammaires locales etde lexiques terminologiques. Nos résultats montrent que cette approche semble viable et nous poussent à élargir cette étude par l’analyse de nouveaux genres textuels.
Keywords: extraction d’informations biographiques; elations sémantiques; grammaires locales; entités nommées; enrichissement du lexique

ProfilPro: Reconstitution automatique d'un profil professionnel à partir des documents du Web - Geierhos, Michaela; Bsiri, Sandra (Linguistics, Computer Science and Language Processing: Festschrift for Franz Guenthner on the Occasion of His 60th Birthday (Tributes 6))

RELAX - Extraction de relations sémantiques dans les contextes biographiques - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Traitement Automatique des Langues (TAL))

Safety of Component-Based Systems: Analysis and Improvement using Fujaba4Eclipse - Tichy, Matthias; Henkler, Stefan; Meyer, Matthias; von Detten, Markus (Companion Proceedings of the 30th International Conference on Software Engineering (ICSE), Leipzig, Germany)

Aspect-oriented modelling from a different angle - Kindler, Ekkart; Schmelter, David (Proceedings of the 2008 AOSD workshop on Aspect-oriented modeling - AOM '08)
In this paper, we report on a new approach of aspect-oriented modelling, which is particularly suited for domains with naturally born aspects as part of that domain: MoDowA for Modelling Domains with Aspects. Though these models are on a very high level of abstraction and could be made early in the development process, these models are fully operational in that they can be executed by an interpreter. This way, we shed a light on Aspect-oriented Modelling from a new, different angle.

Component Story Diagrams in Fujaba4Eclipse - Holtmann, Jörg; Tichy, Matthias (Proc. of the 6th International Fujaba Days 2008, Dresden, Germany)
A current trend in Software Engineering is the development of self-adaptive component-based software architectures. Our modeling approach for component-based software systems Mechatronic UML, integrated in the Fujaba Real-Time Tool Suite plugin for Fujaba4Eclipse, supports self-adaptiveness only to a certain degree. This paper presents tool support for an extension of Mechatronic UML, which facilitates initialization and recon guration of a Mechatronic UML system based on Story Diagrams and thus enables a step towards self-adaptiveness on a structural level.

Graphtransformationen für komponentenbasierte Softwarearchitekturen - Holtmann, Jörg

Component Story Diagrams: A Transformation Language for Component Structures in Mechatronic Systems - Tichy, Matthias; Henkler, Stefan; Holtmann, Jörg; Oberthür, Simon (Proceedings of the 4th Workshop on Object-oriented Modeling of Embedded Real-Time Systems (OMER 4), Paderborn, Germany)
To cope with the high complexity of software in advanced technical systems, the software of these systems is often built in a component-based fashion. The growing usage of self-adaptive techniques leads to sophisticated reconfigurations of the software component structures during runtime. Current modeling approaches for component-based software systems do not include a transformation language for the specification of component structure reconfigurations. In this paper we therefore introduce an extension of a component-based modeling approach. This extension enables (1) the specification of hierarchical component structures and (2) the specification of structural transformations based on the specified hierarchical component structures. Further, as we consider mechatronic systems, we also show the predictable runtime behavior of the transformations.

Graphtransformationen für komponentenbasierte Softwarearchitekturen - Holtmann, Jörg

Optical resonances of bowtie slot antennas and their geometry and material dependence - Guo, Hongcang; Meyrath, Todd P.; Zentgraf, Thomas; Liu, Na; Fu, Liwei; Schweizer, Heinz; Giessen, Harald (Optics Express)

Three-dimensional optical metamaterial with a negative refractive index - Valentine, Jason; Zhang, Shuang; Zentgraf, Thomas; Ulin-Avila, Erick; Genov, Dentcho A.; Bartal, Guy; Zhang, Xiang (Nature)

Electromagnetic induction in metamaterials - Meyrath, T. P.; Zentgraf, Thomas; Rockstuhl, C.; Giessen, H. (Applied Physics B)

Amplitude- and phase-resolved optical near fields of split-ring-resonator-based metamaterials - Zentgraf, Thomas; Dorfmüller, J.; Rockstuhl, C.; Etrich, C.; Vogelgesang, R.; Kern, K.; Pertsch, T.; Lederer, F.; Giessen, H. (Optics Letters)

Near-field–induced tunability of surface plasmon polaritons in composite metallic nanostructures - CHRIST, A.; LÉVÊQUE, G.; MARTIN, O. J. F.; Zentgraf, Thomas; KUHL, J.; BAUER, C.; GIESSEN, H.; TIKHODEEV, S. G. (Journal of Microscopy)

A System for Aggregated Visualization of Multiple Parallel Discrete Event Simulations - Suess, Tim; Huber, Daniel; Fischer, Matthias; Laroque, Christoph; Dangelmaier, Wilhelm (IEEE International Symposium on Parallel and Distributed Processing with Applications)
In this paper we present a system for the simultaneous visualization of several parallel executed simulation replications. By aggregating the scenes of multiple similar simulations into one single scene it is possible to make a visual statistical analysis of a set of discrete event simulations as well as to easily compare different system parameterizations. The aim of our system is to enhance the model analysis, verification and validation process in terms of speed and ease. The parallel execution of several simulations of complex models and the visualization of these cannot be done on one computer, thus a parallel approach is necessary. Our system uses a thin-client and multiple processors on a PC-cluster. The rendering and the simulation execution are done on processors of the cluster. The client is used only for the visualization of the images transmitted by the cluster and for user interaction.

Resonances in complementary metamaterials and nanoapertures - Rockstuhl, Carsten; Zentgraf, Thomas; Meyrath, Todd P.; Giessen, Harald; Lederer, Falk (Optics Express)

Transition from thin-film to bulk properties of metamaterials - Rockstuhl, Carsten; Paul, Thomas; Lederer, Falk; Pertsch, Thomas; Zentgraf, Thomas; Meyrath, Todd P.; Giessen, Harald (Physical Review B)

Methodisches Denken im Kontext. Festschrift für Christian Thiel, mit einem unveröffentlichten Brief Gottlob Freges

The European Integrated Project "Dynamically Evolving, Large Scale Information Systems (DELIS) - Meyer auf der Heide, Friedhelm

Appropriateness in Discourse: The adjectives surprised and surprising in monologue and dialogue - Mindt, Ilka (Journal of Pragmatics)

Adjective complementation by that-clauses: the relation between the semantics of adjectives and the verb phrase in the that-clause - Mindt, Ilka (Anglistik. International Journal of English Studies)

Aggregated 3D-visualization of a distributed simulation experiment of a queuing system - Dangelmaier, Wilhelm; Fischer, Matthias; Huber, Daniel; Laroque, Christoph; Suess, Tim (2008 Winter Simulation Conference)
The paper describes an approach for an aggregated animation of a simulation experiment in an interactive 3D environment, visualizing multiple, distributed simulation runs. Although the general approach of a 3-dimensional visualization of material flow simulation helps to understand the dynamic behavior of a system better as well as faster, it remains unclear, how typical the animated simulation represents the model, if there is a stochastic influence for even some parameters. By the integrated visualization of multiple distributed simulation runs, this uncertainty can be solved, which will be shown in this paper for a typical simulation study of a queuing system.

Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

The Kinetic Facility Location Problem - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Proceedings of the 11th Scandinavian Workshop on Algorithm Theory (SWAT))

The Kinetic Facility Location Problem - Gehweiler, Joachim; Lammersen, Christiane; Degener, Bastian (Proceedings of the 24th European Workshop on Computational Geometry)
We present a deterministic kinetic data structure for the facility location problem that maintains a subset of the moving points as facilities such that, at any point of time, the sum of the maintenance cost for the facilities and the connection cost for the clients is at most a constant factor larger than the current optimal cost. In our scenario, each point can open a facility and moves continuously along a known trajectory in a d-dimensional Euclidean space where d is a constant. Our kinetic data structure has a storage requirement of O(n (log^d(n)+log(nR))), where n is the number of points and R is the ratio of the product of the maximum maintenance cost and demand to the product of their corresponding minimum values. In the case that each trajectory can be described by a bounded degree polynomial, the data structure processes O(n^2 log^2(nR)) events, each requiring only O(log(nR)) facility changes and O(log^(d+1)(n) log(nR)) time. This results in a total processing time of O(n^2 log^(d+1)(n) log^3(nR)). To the best of our knowledge, this is the first kinetic data structure for the facility location problem.

„Kulturelles Erbe: Denkmalpflege, Restaurierung, Authentizität, Wiederaufbau“ - Seng, Eva- Maria (ForschungsForumPaderborn)

„Modern oder gothisch – gothisch und antique römische Architectur vermischt“ – die Vorschläge zu Wiederaufbau und Rekonstruktion des Speyrer Doms 1771 - Seng, Eva- Maria (Reibungspunkte. Ordnung und Umbruch in Architektur und Kunst. Festschrift zum 65. Geburtstag von Hubertus Günther)

„… Der Hauptzweck ist, die große Welt … allhier im kleineren beisammen zu haben“. Kunst- und Wunderkammern als Bildungseinrichtungen - Seng, Eva- Maria (Hallesche Beiträge zur Europäischen Aufklärung)

Der nahe Spiegel. Vormärz und Aufklärung

Thomas Valentin Lesebuch (Edition) - Eke, Norbert Otto; Olasz-Eke, Dagmar

An O(log n) dominating set protocol for wireless ad-hoc networks under the physical interference model - Scheideler, Christian; W. Richa, Andréa; Santi, Paolo (Proceedings of the 9th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2008, Hong Kong, China, May 26-30, 2008)

Humus Büchner: Dantons Tod in/und Heiner Müllers Der Auftrag - Eke, Norbert Otto (Büchner Jahrbuch 11 (2005-08))

„Gott schütz uns vor den guten Menschen“. Reinigungsrituale und Beschämungsstrategien im deutsch-jüdischen Verhältnis - Eke, Norbert Otto (Schuld und Scham)

„Aber die Liebe? Aber der Tod?“ Judith Kuckarts Prosa - Eke, Norbert Otto (Literatur in Westfalen. Beiträge zur Forschung 9)

Geschichtsprojektionen. Rekurse auf das 18. Jahrhundert und die Konstruktion von ‚Aufklärung’ im deutschen Vormärz - Eke, Norbert Otto; Bunzel, Wolfgang; Vaßen, Florian (Der nahe Spiegel. Vormärz und Aufklärung)

„Man muß die Deutschen mit der Novelle fangen“. Theodor Mundt, die Poesie des Lebens und die „Emancipation der Prosa“ im Vormärz - Eke, Norbert Otto (Der nahe Spiegel. Vormärz und Aufklärung)

„Auf des Degens Spitze die Welt jetzt steht“. Heiner Müller liest Schiller - Eke, Norbert Otto („Verteufelt human“? Zum Humanitätsideal der Weimarer Klassik)

Orient und Okzident. Mohammed, der Islam und das Christentum. Zur Darstellung kultureller Alterität um 1800 (mit einem Seitenblick auf die Bestände der Fürstlichen Bibliothek Corvey) - Eke, Norbert Otto (Der Deutschen Morgenland. Bilder des Orients in der deutschen Literatur und Kultur von 1770-1850)

„In jeder Sprache sitzen andere Augen“. Herta Müllers ex-zentrisches Schreiben - Eke, Norbert Otto (Unterwegs. Zur Poetik des Vagabundentums im 20. Jahrhundert)

Nachwort - Eke, Norbert Otto; Olasz-Eke, Dagmar (Thomas Valentin Lesebuch. Zusammengestellt und mit einem Nachwort von Norbert Otto Eke und Dagmar Olasz-Eke)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland

Taschenbuch der Algorithmen - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Redundant Data Placement Strategies for Cluster Storage Environments - Brinkmann, André; Effert, Sascha (Proc. Int. Conf. on Principles Of DIstributed Systems (OPODIS))

Employing WS-BPEL Design Patterns for Grid Service Orchestration using a Standard WS-BPEL Engine and a Grid Middleware - Brinkmann, André; Gudenkauf, Stefan; Hasselbring, Wilhelm; Höing, André; Karl, Holger; Kao, Odej; Nitsche, Holger; Scherp, Guido (Proc. Cracow Grid Workshop (CGW))

Virtual Supercomputer for HPC and HTC - Birkenheuer, Georg; Brinkmann, André; Dömer, Hubert; Effert, Sascha; Konersmann, Christoph; Niehörster, Oliver; Simon, Jens (Proc. Gemeinsamer Workshop der GI/ITG Fachgruppen "Betriebssysteme" und "KuVS": Virtualized IT infrastructures and their management)

A method for OSEM PET reconstruction on parallel architectures using STIR - Beisel, Tobias; Lietsch, Stefan; Thielemans, Kris (IEEE Nuclear Science Symposium Conference Record (NSS))

Guarantee and Penalty Clauses for Service Level Agreements - Battré, Dominic; Birkenheuer, Georg; Deora, Vikas; Hovestadt, Matthias; Rana, Omer; Wäldrich, Oliver (Proc. Cracow Grid Workshop (CGW))

Layered understanding for sporadic imitation in a multi-robot scenario - Richert, Willi; Niehörster, Oliver; Koch, Markus (Proc. IEEE/RSJ Int.Conf. on Intelligent Robots and Systems (IROS))

Proc. Int. Workshop on Storage Network Architecture and Parallel I/Os (SNAPI)

Computational Steering Of Interactive Material Flow Simulations - Lietsch, Stefan; Zabel, Henning; Laroque, Christoph (Proc. ASME Computers and Information in Engineering Conference (CIE))

The GOmputer: Accelerating GO with FPGAs - Platzner, Marco; Döhre, Sven; Happe, Markus; Kenter, Tobias; Lorenz, Ulf; Schumacher, Tobias; Send, Andre; Warkentin, Alexander (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

CUDA-based, parallel JPEG Compression for Remote Rendering - Lietsch, Stefan; Hermann Lensing, Paul (Proc. Int. Symp. on Image/Video Communications over fixed and mobile networks (ISVC))

Overbooking in Planning Based Scheduling Systems - Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voß, Kerstin (Proc. Int. Conf. on Grid Computing & Applications (GCA))

Data Replication in P2P Environments - Brinkmann, André; Effert, Sascha (Proc. Int. Symp. on Parallelism in Algorithms and Architectures (SPAA))

SelfS – A Real-Time Protocol for Virtual Ring Topologies - Griese, Björn; Brinkmann, André; Porrmann, Mario (Proc. Int. Symp. on Parallel and Distributed Processing (IPDPS))

Recursive Evaluation of Fault Tolerance Mechanisms for SLA Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Proceedings of the 1. GI/ITG KuVS Fachgespräch Virtualisierung

Storage Cluster Architectures - Brinkmann, André; Effert, Sascha (Proc. of the GI/ITG KuVS Fachgespr ̈ach Virtualisierung)

Guiding exploration by combining individual learning and imitation in societies of autonomous robots - Richert, Willi; Klompmaker, Florian; Niehörster, Oliver (Proc. IFIP Conf. on Biologically Inspired Cooperative Computing (BICC))

GPU-Supported Image Compression for Remote Visualization - Realization and Benchmarking - Lietsch, Stefan; Hermann Lensing, Paul (Proc. Int. Symp. on Visual Computing (ISVC))

Computational Steering verteilter, interaktiver Materialflusssimulationen - Laroque, Christoph; Lietsch, Stefan; Zabel, Henning (Augmented & Virtual Reality in der Produktentstehung)

Degree 3 Suffices: A Large-Scale Overlay for P2P Networks - Bienkowski, Marcin; Brinkmann, André; Korzeniowski, Miroslaw (Proc. Int. Conf. on Principles Of DIstributed Systems (OPODIS))

Applying Risk Management to Support SLA Provisioning - Battre, Dominic; Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Cracow Grid Workshop (CGW))

Implementing WS-Agreement in a Globus Toolkit 4.0 Environment - Battré, Dominic; Kao, Odej; Voss, Kerstin (Proc. Usage of Service Level Agreements in Grids Workshop held in conjunction with International Conference on Grid Computing)

Aggregating Robots Compute: An Adaptive Heuristic for the Euclidean Steiner Tree Problem - Hamann, Heiko; Wörn, Heinz (The tenth International Conference on Simulation of Adaptive Behavior (SAB'08))

Spatial Macroscopic Models of a Bio-Inspired Robotic Swarm Algorithm - Hamann, Heiko; Schmickl, Thomas; Wörn, Heinz; Crailsheim, Karl (IEEE/RSJ 2008 International Conference on Intelligent Robots and Systems (IROS'08))
We present a comparative study of two spatially resolved macroscopic models of an autonomous robotic swarm. In previous experiments, the collective behavior of 15 autonomous swarm robots, driven by a simple bio-inspired control algorithm, was investigated: in two different environmental conditions, the ability of the robots to aggregate below a light source was tested. Distinct approaches to predict the dynamics of the spatial distribution were made by two different modeling approaches: one model was constructed in a compartmental manner (ODEs). In parallel, a space-continuous model (PDEs) was constructed. Both models show a high degree of similarity concerning the modeling of concrete environmental factors (light), but due to their different basic approaches, show also significant differences in their implementation. However, the predictions of both models compare well to the observed behavior of the robotic swarm, thus both models can be used to develop further extensions of the algorithm as well as different experimental setups without the need to run extensive real robotic preliminary experiments.